Metagenomic analysis of bacterial community structure and functions during the fermentation of da-jiang, a Chinese traditional fermented food. (July 2020) - Xie, Mengxi; An, Feiyu; Zhao, Yue; Wu, Rina; Wu, Junrui
Abstract: The objective of this study was to understand the role of bacteria during the fermentation of da-jiang, a popular traditional Chinese fermented soybean food. In this study, 15 homemade da-jiang samples were analyzed bacteria community via high-throughput sequencing technology. The sequencing data analysis showed that 248 genera, including 841 species of bacteria, the dominant bacteria were Leuconostoc, Acinetobacter, Enterobacter, Enterococcus, Pantoea, Lactococcus, Lactobacillus, Pseudomonas, Staphylococcus, Tetragenococcus, and Weissella . Furthermore, the functional genes of bacteria during the fermentation are mainly associated with carbohydrate metabolism, amino acid metabolism, membrane transport, inorganic ion transport and metabolism, signal transduction, and metabolism of coenzyme and vitamins. Most the bacteria can participate in primary metabolism, the characteristics of da-jiang related to a few species. Pseudomonas Chlororaphis is closely associated with the color of da-jiang . Pseudomonas fluorescens is closely associated to the production of tyramine and histamine. This information may provide important insight into the microbial community structure and key enzymes in traditional da-jiang and might help elucidate the biological functions of these microbes, as well as their use as a starter culture to obtain high-quality da-jiang . Highlights: The structure of bacterial community in da-jiang was elucidated. Genus Leuconostoc, Acinetobacter and Enterobacter dominated the fermentation. Biological functions of genes from the microbiota were characterized. The precise species involved in the production of lactic acid was identified. Pseudomonas fluorescens is closely related to the production of tyramine and histamine.